Upregulation of CIP2A in estrogen depletion‐resistant breast cancer cells treated with low‐dose everolimus. Issue 10 (3rd September 2020) - Nishio, Eiji; Hayashi, Takanori; Akaza, Mao; Hisatomi, Yukiko; Hikichi, Masahiro; Fujii, Takuma; Utsumi, Toshiaki; Harada, Nobuhiro; Shimono, Yohei
Abstract : Everolimus (EVE), an inhibitor of mammalian target of rapamycin, is an emerging second‐line therapeutic option for hormone therapy‐resistant breast cancers. However, some patients do not respond to EVE, whereas in others it exacerbates the disease. Cellular inhibitor of protein phosphatase 2A (CIP2A) is a human oncoprotein that can promote cancer cell growth and apoptosis resistance. Although CIP2A is upregulated in hormone‐related cancers, such as breast cancer, little is known about potential anti‐tumor effects of downregulating CIP2A. As a model to study the resistance of breast cancer cells to hormone treatment, we previously established clones of long‐term estrogen depletion‐resistant MCF‐7 (LTED) cells. Here, we selected three clones highly responsive to EVE and three clones poorly responsive to EVE. When cells were treated with EVE, CIP2A mRNA expression was decreased in highly responsive EVE clones (DC‐cells) whereas it was increased in poorly responsive EVE clones (IC‐cells). Using Kaplan–Meier survival plots, we report that high expression of CIP2A was associated with significantly reduced overall survival in patients with luminal A breast cancer. In IC‐cells, cell growth was enhanced upon EVE treatment whereas an EVE range of 0.1–100 nm decreased growth in DC‐cells. The mRNA expression of genes involved in epithelial–mesenchymal transition (EMT) such as CDH1, CLDN3, and CK19 was significantly decreased in IC‐cells, but remained unchanged in DC‐cells. These findings highlight a relationship between CIP2A and EMT in the intrinsic resistance of hormone therapy‐resistant breast cancers to EVE. Abstract : Everolimus (EVE) is a drug that improves resistance to hormone therapy but may have adverse effects on EVE‐resistant patients. We indicated that even low concentrations of EVE could increase CIP2A expression in EVE‐resistant breast cancer cells. High CIP2A expression was associated with reduced luminal A breast cancer patient survival. Moreover, the expression of epithelial–mesenchymal transition‐related genes decreased in EVE‐resistant cells.